Sleep quality and cognitive function on self-rated health status among the elderly: Findings from the Indonesian family life survey (IFLS-5) - Asri, Yuni; Zakaria, Amin; Yunita, Heny N.; Azizah, Fidrotin; Sasmiyanto, Sasmiyanto; Murtiyani, Ninik; B. Manga , Yankuba (Narra J, 2024)
Cognitive decline poses a significant challenge for the elderly population globally. The aim of this study was to determine the prevalence of cognitive function and its associated factors among the elderly in the Indonesian family life survey’s fifth wave (IFLS-5) conducted from 2014 to 2015. The study included elderly individuals aged 60 and above, excluding proxy respondents and those with missing data. Various socio-demographic, cognitive function and health-related variables were analyzed, including age, sex, education level, marital status, residence, region, economic status, current employment, self-rated health status, happiness, sleep quality, depression, loneliness, and chronic conditions. Multivariate logistic regression analysis was used to identify the factors associated with cognitive functions among the 2,929 elderly respondents. The results revealed that 44.6% of the respondents reported poor cognitive function. In the unadjusted model, residence (OR: 0.81; 95%CI: 0.70–0.94), region of other islands (OR: 0.66; 95%CI: 0.54–0.81), sleep quality (OR: 0.53; 95%CI: 0.42–0.68), self-rated health status (OR: 1.38; 95%CI: 1.19–1.61), happiness (OR: 1.48; 95%CI: 1.22–1.79), and depression (OR: 1.22; 95%CI: 1.04–1.44) showed significant associations with cognitive function. After adjusting for confounding factors, the association remained significant for residence (OR: 0.77; 95%CI: 0.66–0.89), regions other than Java, Bali, and Sumatra (OR: 0.61; 95%CI: 0.50–0.76), self-rated health  (OR: 1.28; 95%CI: 1.09–1.51), happiness (OR: 1.30; 95%CI: 1.06–1.59), and sleep quality (OR: 0.60; 95%CI: 0.47–0.78). These findings emphasize the necessity of interventions aimed at enhancing sleep quality and overall health in order to preserve cognitive function among the elderly, thus potentially improving their quality of life. Implementing comprehensive health programs could significantly enhance the overall quality of life for the aging population, especially the elderly population.